INFORMATION AND COMMUNICATION TECHNOLOGIES IN COLOMBIAN UNIVERSITIES: EVOLUTION AND FUTUROLOGY (2013)
The current review summarizes the historic memory of the evolution and futurology concerning the Information and Communication Technologies (ICT) in Colombian Universities. This is in order to make an approach to understand the current state and provide a conceptual input that advices decision making, policies and programs regarding ICTs towards its trends in universities. ICTs mean modernization, quality, productivity, better services and support to educational processes. Therefore, some universities try to be up-to-date because they consider that ICTs gives them the advantage, which is why it is imperative to investigate how this process was faced. This synthesis followed the methodology of the History of Education3 . ICTs were integrated in the Colombian universities mainly in the concepts of teaching and management through university’s autonomy, advancing in every context towards an on-line university. Nowadays, the potential and services have become real, there are public policies available and on-line modality is increasing, however the University 2.0 trend must be reached.